A cross-sectional study of emergency department visits by people who inject drugs. Issue 5 (16th July 2012) - Aitken, Campbell; Kerr, Thomas; Hickman, Matthew; Stoové, Mark; Higgs, Peter; Dietze, Paul
Abstract : Background: People who inject drugs (PWID) have worse health than non-injectors and are at heightened risk of incidents that necessitate hospital emergency department (ED) visits. Study objectives: To describe ED visits by PWIDs in Melbourne, Australia, and compare reasons with those given in Vancouver, Canada. Methods: In 2008–2010, 688 Melbourne PWIDs were interviewed about their ED visits; these data were contrasted with published data about ED visits by PWIDs in Vancouver. Results: Participants reported 132 ED visits in the month preceding interview—27.3% drug-related, 20.5% trauma-related (principally physical assault), 13.6% for psychiatric problems. Melbourne PWIDs are less likely to attend ED for soft-tissue injuries, and more likely to attend after physical assault than PWIDs in Vancouver. Conclusion: PWID in Melbourne and Vancouver attend EDs for different reasons; information about PWID visits can help EDs cater for them and provide insights for prevention.